2001
DOI: 10.1046/j.1365-2761.2001.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered tissue distribution of Loma salmonae: effects of natural and acquired resistance

Abstract: This study compared and contrasted the fate of the microsporidian Loma salmonae, a branchial pathogen of salmonids of the genus Oncorhynchus, upon exposure of (1) naive susceptible rainbow trout (RT) O. mykiss, (2) naive RT passively immunized with sera from RT previously exposed to L. salmonae, (3) previously exposed and resistant RT and (4) two species believed to be innately resistant to the parasite, Atlantic salmon (AS) Salmo salar and brook trout (BT) Salvelinus fontinalis. The fish were infected per os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…As for L. salmonae, it has been demonstrated that the parasite penetrates through the gut epithelium and migrates to the heart, where early merogonic stages occur, followed by xenoma formation in the gills (Kent and Speare, 2005). Sanchez et al (2001) suggested that Atlantic salmon and brook trout Salvelinus fontinalis, the resistant species to L. salmonae, did not block the parasite invasion at the entrance in the gut, and that the parasite failed to develop into xenoma inside the fish body. K. takedai is not likely to follow the same migration pattern to L. salmonae, because cyst formation occurred simultaneously at the heart and trunk muscle.…”
Section: Discussionmentioning
confidence: 99%
“…As for L. salmonae, it has been demonstrated that the parasite penetrates through the gut epithelium and migrates to the heart, where early merogonic stages occur, followed by xenoma formation in the gills (Kent and Speare, 2005). Sanchez et al (2001) suggested that Atlantic salmon and brook trout Salvelinus fontinalis, the resistant species to L. salmonae, did not block the parasite invasion at the entrance in the gut, and that the parasite failed to develop into xenoma inside the fish body. K. takedai is not likely to follow the same migration pattern to L. salmonae, because cyst formation occurred simultaneously at the heart and trunk muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The use of an inactivated spore-based vaccine was identified as a necessary first step in the quest for commercial vaccines against microsporidian infections [27]. However, rainbow trout passively immunised with sera from L. salmonae-resistant fish showed a delay in the early stages of the life cycle with the arrival of the parasite in the heart, suggesting that humoral factors played a limited role in the initial immune response [28]. Unfortunately, the precise mechanisms of resistance in fish to microsporidia are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the precise mechanisms of resistance in fish to microsporidia are unknown. However, it has been suggested that a cell-mediated immune response is mounted based on the intracellular nature of L. salmonae [1,13], minimal humoral response [28] and the induction of strong protection in recovered fish [12,13,28]. Similarly, rainbow trout inoculated with either a pathogenic or attenuated vaccine strain of Cryptobia salmositica, a haemoflagellate protozoan, showed strong cell-mediated immune responses during infection as well as during protection against cryptobiosis [18]; cell-mediated immunity increased three weeks following vaccination against C. salmositica and good correlation was observed between cell-mediated immunity and the control of parasitaemia [18].…”
Section: Discussionmentioning
confidence: 99%
“…Passive immunization with serum from resistant fish seems to have a limited or null role in protection against the initial stages of the parasite in the gut. This was observed in naive rainbow trout inoculated with serum from L. salmonae infected fish [72]. Although the presence of transferred Ab delayed parasite infection for just one week, it was attributed to low levels of Ab conferred during the passive Ab administration.…”
Section: Humoral Responsementioning
confidence: 94%